Penerapan Aroma Therapy Bunga (rose centifolia) dan Pijat Bayi Terhadap Durasi Tidur Bayi Usia 3-12 Bulan di RSUD Poso: Application Of Rose Flower Aromatherapy (Rose Centifolia) And Infant Massage On Sleep Duration Of Infants Aged 3-12 Months - Niluh Cindy; Dewi Nurviana Suharto (Madago Nursing Journal, 2023)
Introduction: The impact of sleep disturbances in infants is that the baby becomes often awake and fussy. The importance of sleep time in infants, then the duration of sleep in infants must be completely fulfilled so as not to adversely affect their development. One of the nursing interventions to treat sleep disorders in infants is massage and rose aroma therapy. The purpose of this study was to describe the application of nursing care with massage interventions and rose aroma therapy to increase infant sleep duration. Method : Descriptive research methods with a case study approach. Results : the patient's mother said her child had a cough with phlegm, fever for 3 days, the patient was fussy and restless, the patient slept only ± 8 hours a day, the patient often woke up at night due to coughing, the patient was difficult to sleep well, the patient's face looked pale, often seen yawning, temperature: 38.9 ° C RR 46x / min, pulse 120x / min, there are additional ronchi breath sounds, nursing diagnosis of airway clearance, hyperthermia, sleep pattern disorders. Nursing interventions for airway management, warm compresses, massage therapy and aromatherapy. Implementation of chest physiotherapy measures as well as giving 1ml combiven nebulizer + 2ml Nacl and suctioning. Giving tepid water sponge, doing baby massage and giving rose aroma therapy. The results of the evaluation of the patient's sleep increased from 8 hours to 12 hours a day, the patient was calm, the patient woke up at night only asking for milk and after waking up the patient could fall asleep again, coughing with phlegm was reduced, vesicular breath sounds, temperature: 37°C, RR: 38x/min. Conclusion: giving baby massage and rose aroma therapy can increase the duration of infant sleep. nurses can provide baby massage combined with rose aroma therapy to increase the duration of infant sleep.